Nutritional Value of Eggs in Human Diet - Rafed, Rizwanullah; Abedi, Mohammad Hassan; Mushfiq, Sayed Rahimullah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Poultry is one of the most widespread food industries worldwide. Chicken is the most farmed species, with over 90 million tons of chicken meat produced per year [19]. Eggs have been a human food since ancient times. They are one of nature’s nearly perfect protein foods and have other high-quality nutrients. Eggs are readily digested and can provide a significant portion of the nutrients required daily for growth and maintenance of body tissues. They are utilized in many ways both in the food industry and the home. The term “eggs”, without a prefix, generally relates to chicken eggs and is so considered in this study [23]. Chicken eggs are one of the best sources of high-quality protein along with important vitamins and minerals. In both developed and developing countries an increased egg production and consumption could significantly improve nutritional needs of adults and children. Eggs are also an economical source of nutrients for a healthy diet and life, especially important for the mental development of growing children [19]. The purpose of this study is to describe the nutritional benefits of eggs in the human diet. Hence, in this study methodology/approach; the scientific literature was searched using Medline and key words relevant to eggs, egg nutrients and it is nutritional roles.